DAMPAK SISTEM PENANAMAN TERHADAP KARAKTER TANAH DAN KUALITAS HASIL TANAMAN TEBU DI TANAH PASIRAN - Anna Kusumawati; Rahmi Sabrina Hamami; Wini Aswari Br Barus (Jurnal Penelitian Pertanian Terapan, 2025)
Sugarcane in Indonesia are very important economically because they were the main raw material for the sugar industry. To meet sugar needs, efforts are needed to intensify and extensify sugarcane cultivation, ensuring high productivity and yield. One of the expansions of sugarcane fields in Yogyakarta is fields with sandy soil. The planting system is an intensification effort, both with single rows and double rows, where each system has a different impact. This research aims to analyze the impact of sugarcane planting (single-row and double-row planting systems) on soil conditions and sugarcane yields on sandy land. This research used a one-factor Randomized Block Design (RAK) with two levels of treatment, namely single-row and double-row systems. Each level was repeated 6 times in blocks, with the land area of ​​one block being 50m2, so the total land area used for research was 300 m2. The analysis was carried out when the plants were 6 months old, by taking samples of 5 plants in each experimental unit and analyzing the Brix percentage, pol percentage, purity value, sap value, and yield. Soil samples were taken from a depth of 10-30 cm from each experimental unit and analyzed for moisture content, organic matter, soil pH, cation exchange capacity (CEC), available nitrogen, available phosphorus, and available potassium. The data obtained was then analyzed using a T-test at a 5% level and correlation analysis using SPSS. The planting system did not have a significant effect on organic C, pH, CEC, available nitrogen, available phosphorus, and available potassium of the soil. Single-row sugarcane planting provides higher and significantly different poll%, sap value, and sugarcane yield compared to double-row planting. There was a strong correlation between soil organic matter and the sugarcane yield content obtained (r=0.52). Maintaining soil organic matter is an alternative to maintain and increase the yield and yield of sugar cane plants.